Intermolecular packing and charge transfer in metallofullerene/porphyrin cocrystals. Issue 43 (7th May 2019) - Bao, Lipiao; Wang, Bingzhe; Yu, Pengyuan; Huang, Chenli; Pan, Changwang; Fang, Hongyun; Akasaka, Takeshi; Guldi, Dirk M.; Lu, Xing
Abstract : Charge transfer in metallofullerene/porphyrin cocrystals is revealed for the first time. Abstract : Charge transfer in metallofullerene/porphyrin cocrystals is revealed for the first time. Originated from the different solvents for crystallization, distinct stacking manners are presented in the two types of cocrystals. It is demonstrated that intermolecular packing, next to the nature of the corresponding electron donors and acceptors, dominates the charge transfer processes.